KIR- Ligand Interactions in Hypertensive Disorders in Pregnancy - Stefańska, Katarzyna; Tomaszewicz, Martyna; Dębska-Zielkowska, Joanna; Zamkowska, Dorota; Piekarska, Karolina; Sakowska, Justyna; Studziński, Maciej; Tymoniuk, Bogusław; Adamski, Przemysław; Jassem-Bobowicz, Joanna; Wydra, Piotr; Leszczyńska, Katarzyna; et al. (Frontiers in Immunology, 2022)
Abstract HYPOTHESIS: The activity of Natural Killer (NK) cells is considered an important factor in the tolerance towards foetus in pregnancy. The complications of pregnancy, such as hypertensive disorders (HDP), may be therefore associated with this immune compartment. METHODS: In the current study 41 pregnant women with diagnosed HDPs (Gestational Hypertension; GH or Preeclampsia; PE) and 21 healthy women were included. All the patients were under continuous obstetric care during the pregnancy and labour. The number of mother-child mismatches within Killer Immunoglobulin-like receptors (KIRs), their ligands [MM] and missing KIR ligands [MSL] was assessed. KIRs and their ligands were assessed with Next Generation Sequencing (NGS) and Polymerase Chain Reaction Sequence-Specific Oligonucleotide (PCR-SSO) typing. The subsets of NK cells were assessed with multicolor flow cytometry and correlated to the number of MSLs. RESULTS: The number of MSLs was significantly higher in HDP patients when compared to healthy non-complicated pregnancy patients. Some MSLs, such as those with 2DS2 activating KIR, were present only in HDP patients. The percentage of CD56+CD16-CD94+ NK cells and CD56+CD16-CD279+ NK cells correlated with the number of MSL with inhibiting KIRs only in healthy patients. In HDP patients, there was a correlation between the percentage of CD56-CD16+CD69+ NK cells and the number of MSL with inhibiting and activating KIRs. As compared to the healthy group, the percentage of CD56+CD16-CD279+ NK cells and CD56-CD16+CD279+ NK cells were lower in HDP patients. HDP patients were also characterized by a higher percentage of CD56+CD16+perforin+ NK cells than healthy counterparts. CONCLUSIONS: Patients with HDP were characterized by a higher number of MSLs within KIRs receptors. It seemed that the number of MSLs in the healthy group was balanced by various receptors, such as CD94 or inhibitory CD279, expressed on NK cells. On the other hand, in HDP patients the number of MSLs was associated with the activation detected as the increased level of CD69+ NK cells.